Factor-V Deficiency: A Case Report - Zawar, Asfa; Jiskani, Shahzad Ali; Hasan, Majid; Naseem, Lubna (International Journal of Pathology, 2018)
Coagulation factors are required for the blood to clot along with the platelets in case of injury to the vessel endothelium. Factor V is one of the coagulation factors which is found both in the plasma and the platelet granules. It has both anticoagulant and pro coagulant activities.Deficiency of factor V either congenital or acquired leads to a bleeding tendency in the patient. We here report a patient who was a diagnosed case of factor V deficiency and presented with intra-peritoneal bleed.